Influence Of Safety, Health, Work Accident, Work Spirit And Work Ability On Employee Performance In Planning Agency District Regional Development Labuhan Batu - Dhandi Rizky Pratama; Siti Lam'ah Nasution; Abd Halim (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze The Influence of Safety, Health, Work Accidents, Work Morale and Work Capability on Employee Performance at the Regional Development Planning Agency of Labuhanbatu Regency. The research method used in this research is quantitative. In this study, the population was employees of the Regional Development Planning Agency of Labuhanbatu Regency as many as 60 people. The research sample uses saturated sampling technique by attracting the entire existing population to be used as a research sample witha total of 60 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The research results prove that Safety positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency.Health positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency.Work accident positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency.Spirit at workpositive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency Work ability positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. Safety, Health, Work Accidents, Work Morale And Work Ability simultaneously positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. The coefficient of determination is 0.848, meaning that employee performance can be explained by variables Safety(X1),Health(X2), work accidents (X3), morale (X4) and work ability (X5) of 84.8%, while the remaining 15.2% can be explained by other variables not examined in this study.